Understanding global patterns of domestic cannabis cultivation - Barratt, Monica; Bouchard, M.; Decorte, T.; Frank, V.; Hakkarainen, P.; Lenton, Simon; Malm, A.; Nguyen, H.; Potter, G. (Emerald Group Publishing Limited, 2012)
Purpose – Unlike other plant-based drugs, cannabis is increasingly grown within the country of consumption, requires minimal processing before consumption, and can be easily grown almost anywhere using indoor or outdoor cultivation techniques. Developments in agronomic technologies have led to global growth in domestic cultivation, both by cannabis users for self- and social-supply, and by more commercially-oriented growers. Cross-national research is needed to better understand who is involved in domestic cultivation, the diversity in cultivation practices and motivations, and cultivators’ interaction with the criminal justice system and cannabis control policies. Design/methodology/approach – The article introduces the Global Cannabis Cultivation Research Consortium (GCCRC), describes its evolution and aims, and outlines the methodology of its ongoing cross-national online survey of cannabis cultivation. Findings – Despite differing national contexts, the GCCRC successfully developed a core questionnaire to be used in different countries. It accommodates varying research interests through the addition of optional survey sections. The benefits to forming an international consortium to conduct web-based survey research include the sharing of expertise, recruitment efforts and problem-solving. Research limitations/implications – The article discusses the limitations of using non-representative online sampling and the strategies used to increase validity. Originality/value – The GCCRC is conducting the largest cross-national study of domestic cannabis cultivation to date. The aim is not only to better understand patterns of cannabis cultivation and how they differ between countries but also to build upon online engagement methodology with hidden populations.